Percutaneous Peripheral Nerve Stimulation (Neuromodulation) for Postoperative Pain: A Randomized, Sham-controlled Pilot Study. (July 2021) - Ilfeld, Brian M.; Plunkett, Anthony; Vijjeswarapu, Alice M.; Hackworth, Robert; Dhanjal, Sandeep; Turan, Alparslan; Cohen, Steven P.; Eisenach, James C.; Griffith, Scott; Hanling, Steven; Sessler, Daniel I.; Mascha, Edward J.; et al.
Abstract : Background: Percutaneous peripheral nerve stimulation is an analgesic technique involving the percutaneous implantation of a lead followed by the delivery of electric current using an external pulse generator. Percutaneous peripheral nerve stimulation has been used extensively for chronic pain, but only uncontrolled series have been published for acute postoperative pain. The current multicenter study was undertaken to (1) determine the feasibility and optimize the protocol for a subsequent clinical trial and (2) estimate the treatment effect of percutaneous peripheral nerve stimulation on postoperative pain and opioid consumption. Methods: Preoperatively, an electrical lead was percutaneously implanted to target the sciatic nerve for major foot/ankle surgery ( e.g., hallux valgus correction), the femoral nerve for anterior cruciate ligament reconstruction, or the brachial plexus for rotator cuff repair, followed by a single injection of long-acting local anesthetic along the same nerve/plexus. Postoperatively, participants were randomized to 14 days of either electrical stimulation (n = 32) or sham stimulation (n = 34) using an external pulse generator in a double-masked fashion. The dual primary treatment effect outcome measures were (1) cumulative opioid consumption (in oral morphine equivalents) and (2) mean values of the "average" daily pain scores measured on the 0 to 10 Numeric Rating Scale within the first 7 postoperative days. Results: During the first 7 postoperative days, opioid consumption in participants given active stimulation was a median (interquartile range) of 5 mg (0 to 30) versus 48 mg (25 to 90) in patients given sham treatment (ratio of geometric means, 0.20 [97.5% CI, 0.07 to 0.57]; P < 0.001). During this same period, the average pain intensity in patients given active stimulation was a mean ± SD of 1.1 ± 1.1 versus 3.1 ± 1.7 in those given sham (difference, −1.8 [97.5% CI, −2.6 to −0.9]; P < 0.001). Conclusions: Percutaneous peripheral nerve stimulation reduced pain scores and opioid requirements free of systemic side effects during at least the initial week after ambulatory orthopedic surgery. Abstract : The use of active versus sham percutaneous peripheral nerve stimulation was associated with a reduction in pain scores and opioid consumption in the first 7 days after upper and lower extremity surgery. Peripheral nerve stimulation may also reduce pain's interference with physical and emotional functioning with few side effects.Supplemental Digital Content is available in the text.